Manufatura aditiva por deposição a arco em leito de fluxo: prova de conceito - Mendes, Newton Sérgio Nascimento (2022)
The present work aimed to prove the concept of a novel technique of additive manufacturing of large metal parts and with simple geometry, based on the submerged arc process, called Flux Bed Wire + Arc Additive Manufacturing (FB-WAAM). According to this new concept, instead of the flux being supplied through the torch, a flux layer would be previously spread over the substrate (flux bed) and then the metal layer would be deposited by the submerged arc process (SA). The idea is that the bed supports the flux to remain over the layer during the deposition of contours or slender structures. To simulate this condition, a simple wall-type preform was deposited using an equipment prototype that allowed the formation of the adequate flux bed with adjustable thickness. The preform produced by FB-WAAM was characterized in terms of geometry, chemical composition, microstructure and mechanical properties. By using the FB-WAAM concept was possible to produce a preform with 42 layers free of defects and with appropriate geometry, microstructure and mechanical properties. Based on the results obtained, it can be concluded that the concept of the FB-WAAM technique was satisfactorily proved. The FB-WAAM technique showed potential for manufacturing large metal parts with simple geometries in a rapid and economically efficient way, since high deposition rates can be achieved with the SA process and its consumables tend to be relatively cheaper.